Evaluation of physicochemical and phytochemical properties of Safoof-E-Sana, a Unani polyherbal formulation - Ajazuddin (Medknow Publications, 2010)
BACKGROUND: Although the formulations of the Unani system of medicine are popular, not much scientific work has been reported so far. The present article is an attempt to establish the scientific basis of one of the popular Unani formulations Safoof-ESana, a polyherbal formulation widely used as a laxative. METHODS: Investigations were carried out to study the physicochemical and phytochemical properties of Safoof-E-Sana and its active ingredients. RESULTS AND CONCLUSION: The values of percentage loss on drying, angle of repose, Hausner ratio, and Carr’s index of the formulation were calculated as 8.25 ± 0.582, 27.68, 1.23, and 19 respectively, which indicate that the moisture content of the formulation is within the range and depict good flow characteristics. The total ash, acid- nsoluble ash, and water-soluble ash were found to be 19.146 ± 0.237, 2.351 ± 0.223, and 49.216 ± 0.634, respectively; the value of total ash indicates that the inorganic contents of the formulation are below the limits. Alcoholic and aqueous extracts of the formulation and ingredients were prepared and evaluated for phytochemical analysis and extractive values, and the results show that alkaloids of the formulation are more soluble in water than in alcohol and the higher aqueous extractive value (45.784 ± 0.876) of Unani formulation depicts that water is a better solvent of extraction for the formulation than ethanol.